Deep Learning in Elementary School: Systematic Literature Review - Muhammad Zaidan Fadhlurahman; Irwandani; Deri Firmansyah (Jurnal Penelitian Pendidikan IPA, 2026)
The challenges of 21st-century education require learning approaches that go beyond factual mastery and emphasize deep conceptual understanding and higher-order thinking skills in elementary school students. This study aims to analyze research trends, implementation characteristics, and the impact of the deep learning approach in elementary school learning through the Systematic Literature Review (SLR) method. The literature review process follows the PRISMA protocol, including identification, screening, and eligibility stages. Articles were identified using Publish or Perish software from Google Scholar, Semantic Scholar, and Scopus databases with the keywords “deep learning” and “elementary school” within the publication period of 2020–2025. The initial search yielded 528 articles, which were then filtered using inclusion and exclusion criteria, resulting in 17 empirical research articles indexed by SINTA 1–4 and Scopus for the final analysis. The synthesis shows three main characteristics of deep learning implementation: constructive learning through discussions, projects, and contextual exploration; fun and recreational learning that enhances motivation through educational games and digital media; and reflective learning that develops metacognitive awareness through reflection and evaluation. This approach improves learning outcomes, strengthens critical thinking, creativity, collaboration, communication, and supports metacognitive development in elementary education.